Evaluation of syndromic management guidelines for treatment of sexually transmitted infections in South African women. Issue 9 (19th July 2016) - van der Eem, Lisette; Dubbink, Jan Henk; Struthers, Helen E.; McIntyre, James A.; Ouburg, Sander; Morré, Servaas A.; Kock, Marleen M.; Peters, Remco P.H.
Abstract: Objective: To evaluate the performance of three different guidelines for the management of vaginal discharge syndrome (VDS) for women living in a rural setting in South Africa. Methods: We conducted a secondary analysis of data from a cross‐sectional study in Mopani District, South Africa. The 2015 and 2008 guidelines of the South African Department of Health (DoH) and the most recent WHO guidelines were evaluated for adequate treatment of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium and Trichomonas vaginalis infection. Results: Of the 489 women included in this analysis, 35% presented with VDS according to the DoH and 30% per WHO definition of VDS. Fifty‐six per cent of the women with VDS would be treated adequately for these STI when using the 2015 DoH guideline, whereas 76% ( P = 0.01) and 64% ( P = 0.35) would receive adequate treatment with the 2008 DoH and WHO guidelines, respectively. Of the symptomatic women who tested negative for all four STI, STI treatment would have been indicated for 36% as per 2015 DoH guideline vs . 69% ( P < 0.001) per 2008 DoH and 67% ( P < 0.001) per WHO guidelines. Conclusion: A considerable proportion of symptomatic women infected with these common curable STI would receive adequate treatment when using a syndromic management approach, and significant differences exist between the three guidelines. Many symptomatic women without these STI receive broad‐spectrum antibiotics, so new approaches are needed to improve syndromic STI control.